PENINGKATAN KEMAMPUAN MENULIS TEKS RECOUNT MELALUI METODE MIND MAPPING KELAS VIII D SMP NEGERI 2 MLATI - DS, MAGDALENA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This research aims to improve the ability to write Recount texts using the Mind Mapping method in class VIII D students of SMP Negeri 2 Mlati for the 2022/2023 academic year. This research uses a Classroom Action Research design with two cycles. In cycle I, students create a Mind Mapping by choosing an existing theme. Then the finished Mind Mapping becomes a framework for writing the Recount text. Likewise in cycle II, but with a different theme and revised Mind Mapping. In Mind Mapping, choosing past tense verbs is very important in creating Recount text. The use of colors or symbols also helps activate the brain's imagination. Apart from the results of writing the Recount text, in each cycle the activities of students and teachers were also observed. The results of cycle I, the level of student completion in writing the Recount text was 66%, while in cycle II, it reached 100%, which means that all 29 students in the class achieved a minimum score of 76. exceeding the classical completion target of 85%. It can be added that observations of the two cycles show that students are more active and involved in learning to write Recount texts using the Mind Mapping method. This research can be concluded that the Mind Mapping method can improve the ability to write Recount texts in class VIII D students at SMP Negeri 2 Mlati. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan menulis teks Recount melalui metode Mind Mapping pada siswa kelas VIII D SMP Negeri 2 Mlati Tahun Ajaran 2022/2023. Penelitian ini menggunakan desain Penelitian Tindakan Kelas dengan dua siklus. Pada siklus I, siswa membuat Mind Mapping dengan memilih tema yang ada. Kemudian Mind Mapping yang sudah jadi lalu menjadi kerangka dalam menulis teks Recount. Demikian juga pada siklus II, tetapi dengan tema yang berbeda dan Mind Mapping yang telah direvisi. Pada Mind Mapping, pemilihan kata kerja bentuk lampau sangat penting dalam membuat teks Recount. Penggunaan warna atau simbol juga membantu mengaktifkan imajinasi otak. Disamping hasil menulis teks Recount, pada tiap siklus diamati aktivitas siswa dan guru juga. Hasil dari siklus I, tingkat ketuntasan siswa dalam menulis teks Recount adalah 66%, sedangkan pada siklus II, mencapai 100%, yang berarti semua, 29 siswa di kelas tersebut mencapai nilai minimal 76. melebihi target ketuntasan klasikal 85%. Dapat ditambahkan, dari pengamatan dua siklus menunjukkan siswa lebih aktif dan terlibat dalam belajar menulis teks Recount menggunakan metode Mind Mapping. Penelitian ini dapat disimpulkan bahwa metode Mind Mapping dapat meningkatkan kemampuan menulis teks Recount pada siswa kelas VIII D SMP Negeri 2 Mlati.